Risk factors for anaplasmosis in dairy cows during the peripartum - Silva, Jenevaldo Barbosa da [UNESP]; Fonseca, Adivaldo Henrique da (Springer, 2014)
Anaplasma marginale is endemic in tropical and subtropical areas around the world. Some studies have suggested that cows during peripartum may present a transient immunosuppression state and development of clinical signs of anaplasmosis. The aim of this study was to investigate the relationship between some risk factors and the seroprevalence of A. marginale in dairy cows during peripartum in Rio de Janeiro, Brazil. The risk factors analyzed in association with the prevalence of antibodies against A. marginale in dairy cows were calving season, reproductive experience, breed standard, tick infestations, stocking density, and milk yield. The antibodies against A. marginale were tested in indirect enzyme-linked immunosorbent assays. A primary screening using a 2 x k contingency table of the exposed variables with the outcomes was performed. All variables for which p < 0.20 were included in a fixed effects log regression. The risk factors investigated to anaplasmosis were calving (OR 2.61, IC 1.08-7.63), breed standard (OR 3.83, IC 0.08-0.28), reproductive experience (OR 33.7, IC 2.14-5.16), milk yield (OR 3.9, IC 2.24-7.03), Rhipicephalus microplus infestations (OR 10.3, IC 0.05-0.17), and stocking density (OR 22.3, IC 0.05-0.17). Low titers of antibodies against A. marginale during peripartum had been characterized as a period previous to development of clinical anaplasmosis. Thus, studies on anaplasmosis should consider each farm as an epidemiological unit, where environmental and immunological factors may influence the endemic status of the pathogen.
Keywords: Anaplasma marginale; Cattle; Diagnostics; Peripartum; Serologic testing